(untitled) - Twain, Mark (New York, NY, 1992)
This collection contains my 2 childhood and all-time Twain favorites - Prince & Pauper, and Connecticut Yankee - and added the magical ingredient of a historical romance I never knew Twain had written - Joan of Arc. Now that I have read this as well, I see that it may be even better than the other two!
Keywords: Historical fiction, American,Biographical fiction, American; 19th century,19th century